2006 Florida Land Value Survey - Rodney L. Clouser; Ronald Muraro; Laila Racevskis (EDIS, 2007)
FE687, a 5-page fact sheet by Rodney L. Clouser, Ronald Muraro, and Laila Racevskis, describes the results of a survey conducted in May 2006 to provide an estimate of the value of different types of agricultural land for geographic regions of the state. It describes changes in the survey from past surveys and provides a summary of results. Includes references and tables. Published by the UF Department of Food and Resource Economics, April 2007.